(untitled) (Altre Modernità, 2024)
Ecofeminism, with its roots in intersectional analysis, highlights the connections between dominion over nature and the oppression of women. This analytical category integrates the principles of ecology and feminism, promoting a philosophy that rethinks the social model and positions the individual in relation to others and the natural environment. The eco-dystopian novel by Maria Rosa Cutrufelli, L’isola delle madri, casts an anticipatory light on the impacts on nature and society of a world founded on biocidal and ecocidal principles. It describes a society born from hegemonic politics and economies, focused on immediate gain, detached from life, the earth, and the body. This eco-dystopia, masterfully depicted by Cutrufelli, emerges as a scenario of dark consequences of a post-natural era. Through the lens of ecofeminism, the essay analyzes the central themes of the novel such as the destruction of biodiversity and infertility, the results of a misunderstood concept of development. The study extends beyond the literary text, examining the sociocultural context to explore how eco-dystopia, in addition to being a literary genre, becomes a sharp tool for social and environmental critique.